Unlocking the adenosine receptor mechanism of the tumour immune microenvironment - Han, Yecheng; Dong, Chenshuang; Hu, Mingwang; Wang, Xinmiao; Wang, Guiling (Frontiers in Immunology, 2024)
The suppressive tumour microenvironment significantly hinders the efficacy of immunotherapy in treating solid tumors. In this context, stromal cells, such as tumour-associated fibroblasts, undergo changes that include an increase in the number and function of immunosuppressive cells. Adenosine, a factor that promotes tumour growth, is produced from ATP breakdown and is markedly elevated in the tumour microenvironment. It acts through specific binding to adenosine receptors, with A2A and A2B adenosine receptor being primary drivers of immunosuppression. This paper presents the roles of various adenosine receptors in different tumour microenvironments. This review focus on the function of adenosine receptors in the stromal cells and non-cellular components of the tumour microenvironment. Additionally, we summarize and discuss recent advances and potential trends in using adenosine receptor antagonists combined with immunotherapy.